Zakat dan Pemberdayaan Ekonomi Mustahik: Studi Pada Lembaga Amil Zakat, Infak Dan Shodaqoh Muhammadiyah (LAZISMU) Kabupaten Malang - Rahmad Hakim; Muslikhati Muslikhati; Mochamad Novi Rifa’i (Jurnal Ilmiah Ekonomi Islam, 2020)
This study aims to determine the Zakah utilization on the development of economic of zakah recipients Amil Zakat, Infak and Shodaqoh Muhammadiyah Institutions (LAZISMU) Malang Regency. To achieve the objectives of this research, this research was a quantitative descriptive approach which a research approach that emphasizes the aspect of measurement objectively of social phenomena and produces findings that can be obtained using statistical procedures or other ways of quantification (measurement). Data collection methods used are various data collection methods, including: interview and documentation methods, and data analysis used content analysis. Based on the result found that found that the utilization of zakat funds at LAZISMU Malang Regency was able to increase the economic empowerment of mustahik based on several indicators: the usefulness of a program, accuracy and objectivity, the scope of a program, cost effectiveness, timeliness, and accountability. While in the aspect of timeliness of reporting, the financial reporting of zakat funds is seems not up to date.